The Effect of Work Stress and Work Environment on Employee Performance - Elna Halawa; Krisnawati Setyaningrum Nugraheni (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2026)
Employee performance is a critical element in organizational success, particularly in labor-intensive industries such as garment manufacturing. This study aims to analyze the effect of work stress (X1) and work environment (X2) on employee performance (Y) in garment industry companies in Semarang Regency. A quantitative descriptive approach with multiple linear regression analysis was employed. The population and sample comprised 96 employees using total sampling. Data were collected through a Likert-scale questionnaire (1–5) with 10 items per variable. All classical assumption tests (normality, multicollinearity, heteroscedasticity) were satisfied. Reliability tests yielded Cronbach's Alpha of 0.866 (work stress), 0.941 (work environment), and 0.937 (employee performance), confirming instrument reliability. Results indicate: (1) work stress has no significant partial effect on employee performance (t = 1.581; sig. = 0.117); (2) work environment has a significant positive partial effect on employee performance (t = 9.618; sig. = 0.000); (3) simultaneously, both variables significantly affect employee performance (F = 56.630; sig. = 0.000) with a coefficient of determination (R²) of 54.9%. These findings confirm that optimizing the work environment both physical and non-physical is the primary strategic priority for enhancing employee performance in the garment industry.